Effects of a Nursing Education Program Using Virtual Reality for Childbirth Nursing Care on Knowledge, Problem-Solving Ability and Nursing Performance in Nursing Students. - Sung Jung Hong; Hwal Lan Bang; Ferencsik, Leesuk (Journal of Korean Academy of Fundamentals of Nursing, 2025)
Purpose: This study evaluated the impact of integrating virtual reality (VR) and high-fidelity simulation (HFS) in childbirth nursing education on nursing students' knowledge, problem-solving ability, nursing performance, and learning satisfaction. Methods: A non-equivalent control group pretest-posttest quasi-experimental design was used. The participants included 41 third-year nursing students, with 21 in the experimental group and 20 in the control group. The experimental group received VR and HFS education, while the control group received HFS alone. The interventions were conducted over 3 weeks, and data collection occurred between May and August 2022. Results: The experimental group showed significant improvements in knowledge, problem-solving ability, and nursing performance compared to the control group. Learning satisfaction was also significantly higher in the experimental group. Conclusion: Integrating virtual reality into nursing education can improve learning outcomes and increase satisfaction. Expanding VR-based practical training programs is vital to addressing clinical site shortages and improving educational outcomes.